THE IMPACT OF MACROECONOMICS AND CAPITAL STRUCTURE ON COMPANY VALUE THROUGH FINANCIAL PERFORMANCE AND COMPANY SIZE IN THE BASIC MATERIAL SECTOR OF THE INDONESIAN STOCK EXCHANGE (2021–2024). - Marli Marli (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the indirect influence between macro fundamental variables, capital structure, financial performance, firm size, and firm value. Method: This explanatory quantitative research type adopts Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the mediation relationship and reveals.Result: The findings of macro fundamentals have a significant positive effect on financial performance and firm size but its indirect effect on firm value through firm size is negative, capital structure shows a paradox of indirect influence - negative through financial performance but positive through firm size. These findings highlight three main theoretical contributions: first, the validation of a firm valuation model that integrates complex mediation effects. The research gap identified is the need to explore moderating variables such as corporate governance and industry characteristics that may influence the dynamics of this indirect relationship. Keywords: Capital Structure, Financial Performance, Firm Size, And Firm Value